Inorganic and organic trace mineral supplementation in weanling pig diets - Thomaz, Maria C. [UNESP] (2015)
A study was conducted to evaluate the s of dietary inorganic and organic trace minerals in two levels of supplementation regarding performance, diarrhea occurrence, hematological parameters, fecal mineral excretion and mineral retention in metacarpals and liver of weanling pigs. Seventy piglets weaned at 21 days of age with an average initial body weight of 6.70 ± 0.38 kg were allotted in five treatments: control diet (no added trace mineral premix); 50% ITMP (control diet with inorganic trace mineral premix supplying only 50% of trace mineral requirements); 50% OTMP (control diet with organic trace mineral premix supplying only 50% of trace mineral requirements); 100% ITMP (control diet with inorganic trace mineral premix supplying 100% of trace mineral requirements); and 100% OTMP (control diet with organic trace mineral premix supplying 100% of trace mineral requirements). Feed intake and daily weight gain were not affected by treatments, however, piglets supplemented by trace minerals presented better gain:feed ratio. No differences were observed at calcium, phosphorus, potassium, magnesium, sodium and sulfur excreted in feces per kilogram of feed intake. Treatments did not affect calcium, phosphorus, magnesium, sulfur and iron content in metacarpals. Trace mineral supplementation, regardless of level and source, improved the performance of piglets.